Agro Morphological Trait and Yield Component Evaluation of Malt Barley (Hordeum Distichon L.) Varieties Response to the Rate of Fertilizer in Habro Woreda West Hararghe Zone, Oromia, Ethiopia (Indian Journal of Advanced Botany (IJAB), 2024)
The study assessed the effects of NPSB Fertilizer Rate on Yield and morphological traits of Malt barley Varieties. The experiment used a Randomized Complete Block Design with three varieties and five levels of fertilizer rates. The effects of NPSB fertilizer rate and varieties were highly significant on all yield components; phenology and morphological traits. The highest number of kernels per spike (29.5), above ground biomass (12.0 tha-1), and straw yield (6.4 tha-1) were obtained from 200kg NPSB ha-1 , while highest the thousand grain weights (48.2g) were obtained from 150kg NPSB ha-1. The interaction effects of varieties and fertilizer rates were significant at p<0.05 on grain yield (5653.3) from the Traveller variety at 150 kg NPSB ha-1 fertilizer rates. The analysis of variance showed that the interaction effects of varieties and fertilizer rates were significant at p<0.05 on Hectoliter (69.133) from the Traveller variety at 150 kg NPSB ha-1 fertilizer rates. Finally, from the above result, it can be concluded that using 150 kg ha-1 NPSB fertilizer with Traveller variety can be recommended for malt barley production in the study area.